Egyptian treasures from the Egyptian Museum in Cairo (1999)
An in-depth study of artifacts in the Matḥaf al-Miṣrī (known in America as the the Egyptian Museum in Cairo).
Includes bibliographical references (pages 413-416)
UPSA-1831g donated by Dr. Victor Paz
Keywords: Art, Egyptian -- Catalogs; Art -- Egypt -- Cairo -- Catalogs; Egypt -- Antiquities -- Catalogs